On Darboux vector in Lorentzian 5-space - Iyigün, E. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We introduce the Darboux vector in the Lorentzian 5-space. We give some characterizations of this vector in the space. Inaddition, we consider some special cases in the space.